Preventive Effect of Limosilactobacillus fermentum SCHY34 on Lead Acetate-Induced Neurological Damage in SD Rats - Long, Xingyao; Wu, Haibo; Zhou, Yujing; Wan, Yunxiao; Kan, Xuemei; Gong, Jianjun; Zhao, Xin (Frontiers in Nutrition, 2022)
Lead poisoning caused by lead pollution seriously affects people's health. Lactic acid bacteria has been shown to be useful for biological scavenging of lead. In this experiment, Sprague-Dawley (SD) rats were treated with 200 mg/L of lead acetate solution daily to induce chronic lead poisoning, and oral Limosilactobacillus fermentum (L. fermentum) SCHY34 to study its mitigation effects and mechanisms on rat neurotoxicity. The L. fermentum SCHY34 showed competent results on in vitro survival rate and the lead ion adsorption rate. Animal experiments showed that L. fermentum SCHY34 maintained the morphology of rat liver, kidney, and hippocampi, reduced the accumulation of lead in the blood, liver, kidney, and brain tissue. Further, L. fermentum SCHY34 alleviated the lead-induced decline in spatial memory and response capacity of SD rats, and also regulated the secretion of neurotransmitters and related enzyme activities in the brain tissue of rats, such as glutamate (Glu), monoamine oxidase (MAO), acetylcholinesterase (AchE), cyclic adenosine monophosphate (cAMP), and adenylate cyclase (AC). In addition, the expression of genes related to cognitive capacity, antioxidation, and anti-apoptotic in rat brain tissues were increased L. fermentum SCHY34 treatment, such as brain-derived neurotrophic factor (BDNF), c-fos, c-jun, superoxide dismutase (SOD)1/2, Nuclear factor erythroid 2-related factor 2 (Nrf2), and B-cell lymphoma 2 (Bcl-2), and so on. L. fermentum SCHY34 showed a great biological scavenging and potential effect on alleviating the toxicity of lead ions.